Spontaneous Internal Pancreatic Fistulae Complicating Acute Pancreatitis. (6th July 2021) - Singh, Amandeep; Aggarwal, Manik; Garg, Rajat; Walsh, Matthew; Stevens, Tyler; Chahal, Prabhleen
Abstract : Spontaneous pancreatic fistula (PF) is a rare but challenging complication of acute pancreatitis (AP). The fistulae could be internal (draining into another viscera or cavity, e.g., pancreaticocolonic, gastric, duodenal, jejunal, ileal, pleural, or bronchial) or external (draining to skin, i.e., pancreaticocutaneous). Internal fistulae constitute the majority of PF and will be discussed in this review. Male sex, alcohol abuse, severe AP, and infected necrosis are the major risk factors for development of internal PF. A high index of suspicion is required to diagnose PF. Broad availability of computed tomography makes it the initial test of choice. Magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography have higher sensitivity compared with computed tomography scan and also allow for assessment of pancreatic duct for leak or disconnection, which affects treatment approaches. Certain complications of PF including hemorrhage and sepsis could be life-threatening and require urgent intervention. In nonurgent/chronic cases, management of internal PF involves control of sepsis, which requires effective drainage of any residual pancreatic collection/necrosis, sometimes by enlarging the fistula. Decreasing fistula output with somatostatin analogs (in pancreaticopleural fistula) and decreasing intraductal pressure with endoscopic retrograde cholangiopancreatography or endoscopic ultrasound/interventional radiology–guided interventions or surgery are commonly used strategies for management of PF. More than 60% of the internal PF close with medical and nonsurgical interventions. Colonic fistula, medical refractory-PF, or PF associated with disconnected pancreatic duct can require surgical intervention including bowel resection or distal pancreatectomy. In conclusion, AP-induced spontaneous internal PF is a complex complication requiring multidisciplinary care for successful management.